Coeficientes de Digestibilidade e Valores de Aminoácidos Digestíveis de Alguns Ingredientes para Tilápia do Nilo (Oreochromis niloticus) - Furuya, Wilson Massamitu; Pezzato, Luiz Edivaldo [UNESP]; Pezzato, Antônio Celso [UNESP]; Barros, Margarida Maria [UNESP]; De Miranda, Edma Carvalho (My University, 2001)
This study was carried out to determine the apparent digestibility coefficients (ADC) of amino acids for corn, wheat bran, soybean meal and fish meal in Nile tilapia (Oreochromis niloticus), juveniles (25.24 ± 3.88 g), fed purified pelletized reference diet containing 33.78% crude protein and 0.10% of chromic oxide (indicator). The average ADC of amino acids were: 88.31; 77.40; 91.78 and 82.58% for corn, wheat meal, soybean meal and fish meal, respectively. Althought results suggest that the protein ADC value is indicative of amino acids ADC, there was variability in individual amino acid digestibility within and among the tested feeds. The results suggest that use of digestible values of amino acids should be use for more accurate and economical feed formulation.
Digestibility Coefficients and Digestible Amino Acids Values of Some Ingredients for Nile Tilapia (Oreochromis niloticus)
Keywords: Amino acids; Apparent digestibility; Feedstuffs; Nile tilapia; Oreochromis niloticus